The Influence of Leadership Style, Discipline, and Work Training on the Performance of Civil Servants at the Department of Communication, Informatics, Statistics, and Encryption - Hamdani, Dodi; Wardi, Jeni; Yunefri, Yogi (South East Asian Management Concern, 2024)
This research was conducted to analyze the extent of the influence of leadership style, work discipline, and training on employee performance at the Meranti Islands Regency Communications, Information, Statistics, and Coding Service to analyze the extent of the influence of leadership style, work discipline, and training simultaneously on employee performance in the Department Informatics Communication, Statistics, and Coding, Meranti Islands Regency. Data collection techniques through observation, questionnaires, and documentation, with data analysis techniques using research instrument tests, classical assumption tests, multiple regression analysis, and hypothesis testing. The research results found that leadership style, work discipline, and training had a positive and significant influence on employee performance at the Meranti Islands Regency Communications, Information, Statistics, and Coding Service. Based on the results of the correlation coefficient analysis, it can be concluded that leadership style, work discipline, and training have a simultaneous or joint influence on improving employee performance at the Meranti Islands Regency Communications, Information, Statistics, and Coding Service. So it can be said that the fourth hypothesis proposed is proven to be true